Grain boundary mediated plasticity: A blessing for the ductility of metallic thin films?. (15th August 2021) - Liebig, Jan P.; Mačković, Mirza; Spiecker, Erdmann; Göken, Mathias; Merle, Benoit
Abstract: The limited ductility of metallic thin films (< 1%) poses a challenge to MEMS and flexible electronics applications. Here, we report on freestanding gold specimens with the remarkable ability to accommodate ≥10% plastic deformation while retaining a high strength. Using in situ nanomechanical testing in a transmission electron microscope, this exceptionally high ductility is traced back to the combination of an ultrathin thickness, a columnar microstructure and a (111) fiber texture. Under such conditions, the deformation is largely mediated by grain boundaries through grain boundary sliding and shear coupled grain boundary migration. Because these non-conventional mechanisms preserve the cross-sectional thickness of the specimens, necking is postponed and the samples can reach a high ductility. Since the mechanisms were evidenced at room temperature and under strain-rate conditions typical of most applications, the findings open up promising outlooks for developing ductile metallic films by microstructural engineering.